The Archive Office: Structure and Objectives - Gopalswamy, M.; Saraswathi, P. (Journal of Information and Knowledge, 2008)
This article provides an overview of Archives Office as a part of information centres. This study briefs about importance of archives institution, need for archival institution. It shows an overview of the interrelationships of objectives, programmes and service division and staffing structure in a local archives office which may develop in an office.